Effectiveness of KIPAS Counseling in Reducing Students' Academic Procrastination - Farid, Dimas Ardika Miftah; Nursalim, Mochamad; Winingsih, Evi (citeus, 2025)
Academic procrastination is a common issue that hinders students' academic success and psychological well-being. In junior high school, where self-control is still developing, students are particularly vulnerable to distractions and delay in completing academic tasks. To address this issue, counseling approaches grounded in cultural values may offer effective solutions. This study aims to measure the effectiveness of KIPAS (Intensive Progressive Adaptive Structure Counseling) in reducing academic procrastination in junior high school students. A quasi-experimental design with pretest and posttest measurements was employed, involving seven students who exhibited high levels of academic procrastination. The measurement scale used assessed the amanah dimension, which is linked to students' sense of responsibility in completing academic tasks. The results indicated a significant decrease in academic procrastination following the KIPAS counseling intervention, as reflected in the shift between pretest and posttest scores. The Wilcoxon test yielded a Z = -2.429, p = 0.031, suggesting that the change in procrastination levels was statistically significant. These findings support the effectiveness of KIPAS counseling, which integrates local cultural values such as amanah, istiqomah, and iffah, in reducing academic procrastination. This counseling approach fosters students' discipline and responsibility, helping them develop better academic habits. Based on the results, it is recommended that KIPAS counseling be implemented in diverse educational settings to further assess its effectiveness. Schools should consider adopting culturally based counseling approaches to help address procrastination, improve learning outcomes, and enhance students' psychological well-being.